Divided Government and the Fragmentation of American Law. Issue 2 (1st May 2015) - Farhang, Sean; Yaver, Miranda
Abstract : We investigate institutional explanations for Congress's choice to fragment statutory frameworks for policy implementation. We argue that divided party government, which fuels legislative‐executive conflict over control of the bureaucracy, motivates Congress to fragment implementation power as a strategy to enhance its control over implementation. We develop a novel measure of fragmentation in policy implementation, collect data on it over the period 1947–2008, and test hypotheses linking separation‐of‐powers structures to legislative design of fragmented implementation power. We find that divided party government is powerfully associated with fragmentation in policy implementation, and that this association contributed to the long‐run growth of fragmentation in the postwar United States. We further find that legislative coalitions are more likely to fragment implementation power in the face of greater uncertainty about remaining in the majority.